BdLT-Seq as a barcode decay-based method to unravel lineage-linked transcriptome plasticity - Yelyzaveta Shlyakhtina; Bianca Bloechl; Maximiliano M. Portal (Nature Communications, 2023)
Cellular plasticity is a core biological process; however, observing diversity in non-genetic inheritance and the resulting phenotypic outputs, is challenging. Here the authors develop a non-genetically based tracing technology which can be used to reveal lineage-linked transcriptome plasticity.